Family Planning and Legal Change: A Cross-Cultural Study Inspired by Ibn Qayyim in Egypt and Indonesia - Fattah, Salman; Misbahuddin; Kurniati; Amal Ashraf (DIKTUM: Jurnal Syariah dan Hukum, 2025)
This study addresses the challenges of integrating Islamic jurisprudence with family planning policies in Egypt and Indonesia, two Muslim-majority countries with distinct socio-political contexts. The research aims to analyze the alignment and divergence of these policies with Islamic legal principles, focusing on the practical application of Ibn Qayyim’s legal philosophy. Employing a qualitative approach, the study combines semi-structured interviews, focus group discussions, observations, and document analysis to gather comprehensive data from over 50 stakeholders and 100 legal and policy documents. Findings reveal that while Egypt’s centralized governance benefits from Al-Azhar’s religious endorsements, rural resistance highlights cultural challenges. In Indonesia, decentralized governance fosters regional diversity, but inconsistent fatwa issuance complicates policy implementation. The study contributes practically by recommending enhanced collaboration between policymakers and religious leaders and theoretically by extending Ibn Qayyim’s framework to contemporary governance. Its novelty lies in its cross-cultural approach, demonstrating how Islamic legal principles can adapt to diverse societal needs through balanced and context-sensitive reasoning